Buildings promote higher incubation temperatures and reduce nest attentiveness in a Neotropical thrush. (9th July 2020) - Batisteli, Augusto F.; De Souza, Leonardo B.; Santieff, Isadora Z.; Gomes, Guilherme; Soares, Talita P.; Pini, Marianela; Guillermo‐Ferreira, Rhainer; Pizo, Marco A.; Sarmento, Hugo
Abstract : Incubation is an energetically costly parental task of breeding birds. Incubating parents respond to environmental variation and nest‐site features to adjust the balance between the time spent incubating (i.e. nest attentiveness) and foraging to supply their own needs. Non‐natural nesting substrates such as human buildings impose new environmental contexts that may affect time allocation of incubating birds but this topic remains little studied. Here, we tested whether nesting substrate type (buildings vs. trees) affects the temperature inside the incubation chamber (hereafter 'nest temperature') in the Pale‐breasted Thrush Turdus leucomelas, either during 'day' (with incubation recesses) or 'night' periods (representing uninterrupted female presence at the nest). We also tested whether nesting substrate type affects the incubation time budget using air temperature and the day of the incubation cycle as covariates. Nest temperature, when controlled for microhabitat temperature, was higher at night and in nests in buildings but did not differ between daytime and night for nests in buildings, indicating that buildings partially compensate for incubation recesses by females with regard to nest temperature stability. Females from nests placed in buildings exhibited lower nest attentiveness (the overall percentage of time spent incubating) and had longer bouts off the nest. Higher air temperatures were significantly correlated with shorter bouts on the nest and longer bouts off the nest, but without affecting nest attentiveness. We suggest that the longer bouts off the nest taken by females of nests in buildings is a consequence of higher nest temperatures promoted by man‐made structures around these nests. Use of buildings as nesting substrate may therefore increase parental fitness due to a relaxed incubation budget, and potentially drive the evolution of incubation behaviour in certain urban bird populations.